Alfred Kazin's America critical and personal writings - Kazin, Alfred 1915-1998 (HarperCollins, 2003)
Material selected from Kazin's three memoirs accompany a selection of his critical writings.
Includes index
Keywords: Kazin, Alfred <1915-1998>; Kazin, Alfred -- 1915-1998; Geschichte 1900-2000; Literatuurkritiek; Literaturkritik; American literature -- History and criticism -- Theory, etc; American literature -- 20th century -- History and criticism; Critics -- United States -- Biography; Literatur; USA; United States -- Civilization -- 20th century; Biografie